Development and Diversity of Bacterial Biofilms in Response to Internal Tides, a Case Study off the Coast of Kuwait - Al Senafi, Fahad; Abed, Raeid M. M.; Muthukrishnan, Thirumahal; Anis, Ayal; Al Rawahi, Ahmed N.; Mahmoud, Huda (Frontiers in Marine Science, 2020)
Information pertaining to changes in abundance and composition of microbial communities on offshore platforms in relation to changes in environmental conditions due to internal tides are scarce. In this study, artificial substrata were deployed at two locations on a gently sloping seabed off the coast of Kuwait. The abiotic factors at the two sites were recorded spatially and temporally using time-series measurements and continuous turbulence profiling for 13 days. Results showed variations in water density between the upper and deeper waters with the pycnocline undulating between 6 and 15 m depth at both locations. In the water layer beneath the pycnocline, significant current shear due to the internal tides led to higher turbidity coupled with lower dissolved oxygen (DO) and chlorophyll a concentration. The microbiological data showed a significant decrease in the biofilm total biomass, bacterial counts and phototrophic biomass with increase in depth at both locations. The 16S rRNA amplicon sequence non-metric multidimensional (NMDS) scaling analysis revealed that biofouling bacterial communities affected by depth with Alphaproteobacteriaand Bacteroidetes members dominated upper and deeper water at both locations. The based-ordination analysis revealed that biofouling bacterial communities at 3 m were different than at 15 m, with a percentage of shared Operational taxonomic units (OTUs) ≤64% between locations and between depths. Despite the limitations of the study, the power of the employed system is demonstrated in the results that shed light on the significance of prevailing environmental conditions associated with internal tides in shaping the biofilm community in subtropical offshore water systems.